Factors affecting UiTM Seri Iskandar students' rental decisions for residential properties in Seri Iskandar, Perak - Muhammad Fauzi, Muhammad Syahir (2024)
Bandar Seri Iskandar has witnessed a surge in real estate demand, primarily due to the presence of Universiti Teknologi MARA (UiTM) and Universiti Teknologi Petronas (Ministry of Finance Malaysia, 2011). The township's accessibility and the growing student population make it an attractive option for homebuyers. According to Tony Ng, Hua Yang Bhd Perak branch manager, the rapid development in Seri Iskandar has led to increased job opportunities, further attracting people to the area (The Star, 2012). Despite UiTM Seri Iskandar's efforts to provide adequate on-campus housing, the growing student population outpaces the available hostel accommodations. Current data indicates a significant shortfall, with only 6,266 hostels for 8,674 students, highlighting a critical concern (Razak et al., 2017). This study objectives are to examine the variables influencing students' rental decisions and to identify the most crucial factor among them. The research focuses on non-resident (NR) students at UiTM Seri Iskandar, specifically those renting private housing off-campus. Utilizing a quantitative approach, the study employs questionnaires to gather data on factors influencing rental decisions. The research includes statistical data from Bahagian Hal Ehwal Pelajar (HEP) and four UiTM Seri Iskandar colleges (KPS, KIM, KIS, KCS). A thorough literature review establishes the foundation for the study, aiming to identify key factors such as location, rental costs, supply insufficiency, facilities and amenities, safety, and overall satisfaction. The survey, distributed via the Non-Residents Telegram group, yielded 215 responses out of the targeted 335, achieving a response rate deemed acceptable for the study. The findings will provide insights into the rental decision-making processes of UiTM Seri Iskandar students, aiding in addressing their housing needs